Potensi Filtrat Daun Sukun (Artocarpus altilis) Sebagai Bioinsektisida Lalat Rumah (Musca domestica) - Ani Yuanita; Ngadino .; Suprijandani . (GEMA LINGKUNGAN KESEHATAN, 2021)
Flies is one type of Arthropod insect as a vector and carrier of disease. Control of flies by using chemical insecticides continuously results in resistance to flies and can pollute the environment. Another alternative that can be used is a plant insecticide that is derived from breadfruit leaf plants. Phytochemical results of breadfruit leaves have 1.88% Flavonoids, Saponins 2.26%, and Tanins 1.05%. The purpose of this study was to determine the potential of breadfruit leaf filtrate as a bioinsecticide of house flies (Musca domestica).This type of research uses pure experiments with a post test only control group design with a concentration of 2.5%, 5%, 7.5%, control and 5 replications. The number of house flies used was 375. Data were analyzed using the Kruskal Wallis test.The results showed p 0.05 which means that there were differences in the average death of house flies by using various concentrations of each treatment. Probit test obtained Lethal Concentration (LC50) results at the first hour ie at a concentration of 5.189%, the 12th hour at a concentration of 3.930% and the 24th hour showed a concentration of 3.086%.Suggestions for other researchers can do the same research by comparing with other plants that contain active compounds that have the potential to kill house flies (Musca domestica). Other plants that have higher active compound content can be used as a recommendation for bio-degradable plant-based insecticides.